Epidermal growth factor receptor expression in pretreatment biopsies from head and neck squamous cell carcinoma as a predictive factor for a benefit from accelerated radiation therapy in a randomized controlled trial - (:unkn) unknown (AMER SOC CLINICAL ONCOLOGY, 2005)
Purpose Accelerated repopulation is a main reason for locoregional failure after fractionated radiotherapy for head and neck squamous cell carcinoma (HNSCC). Epidermal growth factor receptor (EGFR) is a key controller of cellular proliferation in HNSCC, which stimulated the current study to look for a direct link between EGFR status and a possible clinical advantage of accelerated radiotherapy. Patients and Methods Immunohistochemical staining for EGFR was performed in 304 patients with available pretreatment tumor biopsy material among 918 patients randomized to receive continuous hyperfractionated accelerated radiotherapy versus conventionally fractionated radiotherapy. The EGFR index was estimated as the proportion of tumor cells with EGFR membrane staining. Results Significant benefit in locoregional tumor control from continuous hyperfractionated accelerated radiotherapy was seen in patients with HNSCC with high EGFR expression (2P =.010) but not in those with low EGFR expression (2P =.85). EGFR status had no significant effect on survival or rate of distant metastases. The EGFR index was significantly associated with histologic grade and microvessel density. There was moderate support for an association between EGFR status and subsite within the head and neck region but no significant association with Ki-67 index, Ki-67 pattern, p53 index, p53 intensity, bcl-2 expression, or cyclin D1 index. Conclusion This study indicates a key role for the EGFR receptor in determining the proliferative cellular response to fractionated radiotherapy in HNSCC. It also shows that we can select the dose-fractionation regime that has the greatest chance of benefiting the patient. These results also encourage further development of EGFR targeting combined with fractionated radiotherapy in HNSCC.
Keywords: CONVENTIONAL RADIOTHERAPY; MOLECULAR CLASSIFICATION; MULTICENTER TRIAL; PROGNOSTIC VALUE; TREATMENT TIME; LUNG-CANCER; REPOPULATION; ONCOLOGY; CHART; FRACTIONATION